2013
DOI: 10.1007/s00216-013-6808-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multidimensional gas chromatography using a heart-cutting device and cryogenic focusing for the determination of benzophenone derivatives in foodstuffs

Abstract: Photoinitiators are used to promote the polymerization process during the curing of varnishes or inks on cartonboard packaging. Depending on storage conditions and shelf life, these substances are able to migrate through the packaging layer into the foodstuff. This type of contamination phenomenon is therefore becoming a critical issue in terms of food safety. In order to tackle this problem, a fast and selective method was developed for the determination of benzophenone and three methylbenzophenone isomers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
(30 reference statements)
2
19
1
Order By: Relevance
“…coatings, adhesives, printing inks and rubber, as an important source of chemical contamination of food. Recent articles have reported occurrence of phthalates (Bononi & Tateo, 2009;Zhang, Noonan, & Begley, 2008), bisphenols (P erez-Palacios, Fern andez-Recio, Moreta, & Tena, 2012), ink photoinitiators (Bugey, Janin, Edder, & Bieri, 2013;Koivikko et al, 2010), fluorescent whitening agents (Chen & Ding, 2006), polyfluorinated compounds (PFC) (Begley et al, 2005;Poothong, Boontanon, & Boontanon, 2012;Trier, Granby, & Christensen, 2011) and biocides (Domeño, Munizza, & Nerín, 2005; Votavov a, Hanu sov a, V apenka, Dobi a s, & Kvasni cka, 2014). Furthermore, EFSA (2012) believes that recycled paper and board represent an important source of mineral oil hydrocarbons (MOH) including both saturated and aromatic fractions (MOSH and MOAH, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…coatings, adhesives, printing inks and rubber, as an important source of chemical contamination of food. Recent articles have reported occurrence of phthalates (Bononi & Tateo, 2009;Zhang, Noonan, & Begley, 2008), bisphenols (P erez-Palacios, Fern andez-Recio, Moreta, & Tena, 2012), ink photoinitiators (Bugey, Janin, Edder, & Bieri, 2013;Koivikko et al, 2010), fluorescent whitening agents (Chen & Ding, 2006), polyfluorinated compounds (PFC) (Begley et al, 2005;Poothong, Boontanon, & Boontanon, 2012;Trier, Granby, & Christensen, 2011) and biocides (Domeño, Munizza, & Nerín, 2005; Votavov a, Hanu sov a, V apenka, Dobi a s, & Kvasni cka, 2014). Furthermore, EFSA (2012) believes that recycled paper and board represent an important source of mineral oil hydrocarbons (MOH) including both saturated and aromatic fractions (MOSH and MOAH, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…GCeMS has been frequently used for the analysis of phthalates (Bononi & Tateo, 2009;Zhang et al, 2008) and PAH or MOAH (Biedermann & Grob, 2015;Bordajandi, Dabrio, Ulberth, & Emons, 2008;Chalbot, Vei, Lykoudis, & Kavouras, 2006), HPLCeMS/MS for bisphenols (Gallart-Ayala, Moyano, & Galceran, 2010;P erez-Palacios et al, 2012) and PFC (Begley et al, 2005Poothong et al, 2012;Trier et al, 2011), whereas ink photoinitiators have been analyzed by both techniques (Bugey et al, 2013;Sagratini et al, 2008;Shen, Lian, Ding, Xu, & Shen, 2009). Derivatization procedures were also developed for bisphenols and PFCA to make them amenable for GCeMS (Dufkov a, Cabala, & Sev cík, 2012;Viñas, Campillo, Martínez-Castillo, & Hern andez-C ordoba, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, the authors concluded that 1-2 % of the BP in the packaging migrated to the food. For foods where the BP levels were below the specific migration limit of 0.6 mg/kg, levels in the corresponding packaging ranged from 5 to 7 mg/kg [116,117]. Other studies have investigated levels of BP in the packaging of a variety of food products [118][119][120][121].…”
Section: Migration Testing For Measuring Uv Photoinitiatorsmentioning
confidence: 99%
“…A lot of work has been done to analyze and investigate the BPs and a variety of determination methods have been used, such as GC , HPLC , GC–MS and LC–MS . Despite having high sensitivity and low detection limits, these methods still need sample enrichment and purification process before analysis of complex real samples.…”
Section: Introductionmentioning
confidence: 99%